La Nouvelle Repartition des Competences entre l’Etat et la Polynésie Française - Peres, Jean (Victoria University of Wellington Law Review, 2004)
On 27 February 2004 the French government completed the process of giving French Polynesia the new status of Pays d’outre mer (overseas country). This article sets out the new division of powers between the French State government, and the French Polynesian government. Jean Peres analyses the areas that the French government has expressly retained in its sphere of competence, in order to assess the true extent of French Polynesian autonomy. He also compares the new arrangement with the law of 12 April 1996 to see how much the French Polynesian authority has been increased.